Supervision in Clinical Practice Indicator: Evidence Based Practice in the Context of Outpatient Surgery - Teixeira, Leonor Olímpia; Teixeira, Ana; Barroso, Cristina; Carvalho, António Luís (Elsevier, 2020)
Clinical supervision and evidence-based practice in nursing should be understood as complementary and indissociable as they go hand in hand towards the same objectives. Therefore, the supervising process should boost the evidence-based practice in order to promote better nursing care. The purpose of this study was to evaluate nurse’s predisposition to incorporate evidence-based practice into their care and to identify barriers to its application with the purpose of proposing contributions for the implementation of a nursing clinical supervision model that encourages the use of the best evidence available into the daily practice. The study is integrated into the research project “SAFECARE – Supervisão Clínica para a segurança e qualidade dos cuidados”. It was developed as an exploratory-descriptive study in an ambulatory surgery unit of a University Hospital in Porto, Portugal. It had a target population of 59 nurses, and it was used the “Evidence-Based Practice Questionnaire” as a method of collecting data. From the 49 questionnaires collected, we find that the subscale “Practices” has an average score of 4.89, the subscale “Attitudes” 5.36 and the subscale “knowledge/skills and competences” 5.08. These results showed that nurses have a low use of evidence-based practice when compared with the level of knowledge, skills and competences shown, although they seem to have a positive attitude towards this subject. These results can be partially explained by the overburden felt by the n urses, which identified the lack of time and motivation, but also inappropriate training and scarcity of team meetings and proper tools in the workplace as barriers
Keywords: Nursing; Evidence-Based Nursing; Evidence-Based Practice; Ambulatory Surgery